1996
DOI: 10.1159/000246276
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Effect of Ultraviolet A on Ornithine Decarboxylase Induction and Dermatitis Evoked by 12-<i>o</i>-Tetradecanoylphorbol-13-Acetate and Its Inhibition by Curcumin in Mouse Skin

Abstract: Background: Previous studies have demonstrated appreciable tumor induction in mouse skin by daily irradiation with high-power long-wavelength ultraviolet A (UVA). Object: The aim of the present study was to examine the enhancing effects of UVA on changes in mouse skin mediated by the tumor promoter 12-o-tetradecanoylphorbol-13-acetate (TPA) by measurement of ornithine decarboxylase (ODC) activity and morphometric analysis. In addition, we examined the inhibitory effects of curcumin, a component of turmeric, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 0 publications
1
31
0
Order By: Relevance
“…54 Both keratinocyte hypertrophy and the increase in ODC induced by 12-O-tetradecanoylphorbol-13-acetate (TPA) (enhancer of H 2 0 2 formation) or TPA þ UVA were prevented by the ROS inhibitor 1 0 -acetoxychavicol acetate 55 or by a vegetal antioxidant. 56 It is well known that UVA does not interact directly with DNA, but instead appears to contribute to DNA damage through ROS, resulting in oxidative DNA modifications, including the formation of 8-oxodG, protein-DNA crosslinking, base loss and strand breaks. 1,46 Decrease in UVAinduced DNA oxidation (8-oxodG) in RE overexpressing CAT is consistent with this notion.…”
Section: Discussionmentioning
confidence: 99%
“…54 Both keratinocyte hypertrophy and the increase in ODC induced by 12-O-tetradecanoylphorbol-13-acetate (TPA) (enhancer of H 2 0 2 formation) or TPA þ UVA were prevented by the ROS inhibitor 1 0 -acetoxychavicol acetate 55 or by a vegetal antioxidant. 56 It is well known that UVA does not interact directly with DNA, but instead appears to contribute to DNA damage through ROS, resulting in oxidative DNA modifications, including the formation of 8-oxodG, protein-DNA crosslinking, base loss and strand breaks. 1,46 Decrease in UVAinduced DNA oxidation (8-oxodG) in RE overexpressing CAT is consistent with this notion.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin protects cultured human cells from radiationinduced DNA damage and this effect may be due to its strong antioxidant properties. 63 Ishizaki et al 64 observed that topical application of curcumin significantly inhibited TPA-and UVAinduced ornithine decarboxylase activity in mouse epidermis. Oguro and Yoshida 65 have also confirmed this investigation and reported that topical application of curcumin inhibits TPA-and UVA-induced gene expression of metalloprotein in the mouse skin and postulate that these chemopreventive effects may be due to its role as an ROS scavenger.…”
Section: Curcuminmentioning
confidence: 99%
“…Topical administration of the curcumin has been represented to enhance glutathione contents and glutathione-S-transferase (GST) activity, and suppresses lipid peroxidation and COX-2 activation in mouse skin and human IGR-39 melanoma cells (Iersel et al, 1996). Also, curcumin has been represented to attenuate the induction of ornithine decarboxylase (ODC) in mouse skin (Ishizaki et al, 1996) and to induce p53-associated apoptotic cell death through the blocking the NF-κB pathway and inhibiting the apoptotic inhibitor XIAP (X-linked inhibitor of apoptosis protein) in human basal carcinoma cells (Jee et al, 1998). These researches suggest that curcumin could be beneficial chemopreventive agent against the skin cancer (F'guyer et al, 2003).…”
Section: Molecular Targets Of Dietary Phytochemicals In Skinmentioning
confidence: 99%